MARKETING ISTRAŽIVANJE OPŠTIH DETERMINANTI IZBORA STUDIJSKOG PROGRAMA DIGITALNI MARKETING OD STRANE STUDENATA AKADEMSKIH STUDIJA - Đokić, Ines; Milićević, Nikola; Đokić, Nenad (International Journal of Economic Practice and Policy, 2022)
Digital marketing is becoming increasingly relevant in business practice. At the same time, there is a growing need to include digital marketing content in the curricula of higher education institutions. Based on the above, this paper sets two goals - to describe the growing application of digital marketing in business practice in general and to explore the general determinants of the choice of the study program by the students at the higher education institution that will start realization of a master’s study program in digital marketing in 2021/22 school year. In the context of the previous objectives, in addition to collecting secondary information, a primary survey was conducted in June 2021 (n = 89). The results of the primary research indicate a pronounced positive acceptance of the study program digital marketing by students, regardless of specific general determinants.